High-efficiency viscosity-reducing warm-mixing agent, preparation method thereof and warm-mixed asphalt mixture
By using high-efficiency viscosity-reducing temperature mixers prepared with raw materials such as Ni-based expanded perlite, fatty amine-modified vermiculite powder, acrylamide-modified nano-silica, etc., the existing warm mixers are solved, and the low-cost and efficient temperature mixing effect is achieved.
Patent Information
- Application Number
- CN202411769219.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
AI Technical Summary
The existing warm mixing agents lead to poor low-temperature delays in asphalt mixtures, insufficient crack resistance, and high preparation cost.
A high-efficiency viscosity-reducing temperature mixer is prepared by blocking cracking reaction and modification treatment.
This warm mixing agent can effectively reduce the mixing temperature of the asphalt mixture, improve low-temperature crack resistance, reduce energy consumption and harmful gas emissions, and reduce preparation costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of asphalt additives, and specifically discloses a high-efficiency viscosity-reducing warm-mix agent, a preparation method thereof, and a warm-mix asphalt mixture. Background Art
[0002] Asphalt pavement has the advantages of high flatness, durability, excellent elasticity, and convenient pavement maintenance, and has quickly replaced cement pavement to become the mainstream of highway pavement. According to statistics, more than 90% of highway pavements in my country use asphalt pavement as the paving structure, especially in the new construction of highway pavement, the proportion of asphalt pavement is close to 100%. At present, most asphalt pavements are still using traditional hot-mix asphalt mixtures as paving materials. The mixing temperature of this type of asphalt mixture is as high as 160℃ or above. The high temperature not only brings huge fuel consumption to the asphalt mixing plant, but also produces a large amount of asphalt smoke during the construction of the mixture, which has an adverse effect on the air quality of the pavement paving site and the health of the construction workers. At the same time, too high a temperature can easily cause asphalt aging, resulting in poor rolling effect of the asphalt mixture, and the pavement void ratio cannot meet the requirements, which buries the hidden dangers of pavement diseases.
[0003] In order to solve the above problems, engineers designed a warm-mix asphalt mixture, which reduces the mixing and construction temperature of the asphalt mixture by adding warm-mix agent, so that the construction temperature is between hot-mix asphalt mixture and cold-mix asphalt mixture, while the pavement performance and construction performance are consistent with hot-mix asphalt mixture. The mixing temperature of this type of asphalt mixture can be reduced to between 120-140℃, which greatly reduces fuel consumption and harmful gas emissions. Warm-mix agent is the most critical material for realizing the warm-mix function of warm-mix asphalt mixture, and plays a decisive role in the various properties of warm-mix asphalt. At present, warm-mix agents are mainly divided into three categories: organic viscosity-reducing warm-mix agent, surfactant warm-mix agent and foamed asphalt viscosity-reducing warm-mix agent. However, organic viscosity-reducing warm-mix agent generally has the problem of poor low-temperature ductility and insufficient crack resistance of asphalt mixture; surfactant warm-mix agent needs to strictly control the addition amount and has a high cost; and foamed asphalt viscosity-reducing warm-mix agent needs to add an asphalt foam generation system, which requires a large equipment investment.
[0004] Based on this, the development of a warm mix agent that is low-cost, easy to operate and has favorable properties for asphalt performance is of great significance for the development of warm mix asphalt materials. Summary of the invention
[0005] Aiming at the problem that the addition of warm mixing agent in the prior art causes poor low-temperature ductility of asphalt, resulting in insufficient crack resistance of asphalt mixture and high cost of preparing warm mixing agent, the present invention provides a high-efficiency viscosity-reducing warm mixing agent, a preparation method and warm mixing asphalt mixture. The present invention uses Ni-based expanded perlite, fatty amine-modified vermiculite powder, acrylamide-modified nano-silicon dioxide, anti-aging agent and waste plastic as raw material components to prepare a low-cost high-efficiency viscosity-reducing warm mixing agent that can effectively improve the low-temperature performance of warm mixing asphalt mixture. The high-efficiency viscosity-reducing warm mixing agent can not only effectively reduce the mixing temperature of the asphalt mixture, but also ensure good adhesion between asphalt and aggregate under the mixing conditions, can not only effectively reduce the mixing temperature of the asphalt mixture, but also make the asphalt mixture have good viscosity at a lower mixing temperature, reduce energy consumption, and effectively reduce the release of harmful gases, which is safer and more environmentally friendly. In addition, the present invention adopts low-cost raw materials such as waste plastic, expanded perlite and vermiculite, which effectively solves the problem of high cost of preparing warm mixing agent in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following specific technical solutions: The first aspect of the present invention provides a high-efficiency viscosity-reducing warm mixing agent, comprising the following raw material components in percentage by weight: 10%-15% Ni-based expanded perlite, 45%-60% fatty amine-modified vermiculite powder, 10%-15% acrylamide-modified nano-silicon dioxide, 3%-5% anti-aging agent and the remainder of waste plastics.
[0007] The present invention designs a Ni-based expanded perlite, the expanded perlite has a honeycomb porous structure inside, can be used as a carrier of a Ni-based catalyst, and is used for catalytic cracking of waste plastics to obtain waste plastic degradation wax, and the waste plastic degradation wax can be used as a viscosity-reducing component to improve the fluidity of asphalt mixtures at lower mixing temperatures. In addition, the expanded perlite has an excellent heat preservation function, can reduce heat loss to a certain extent, is more conducive to the maintenance of warm mixing effects, and improves the low-temperature crack resistance of warm-mix asphalt mixtures. Fatty amines carry amino groups and have certain activity. After vermiculite is modified with fatty amines, the surface hydrophilicity of vermiculite is reduced, and the hydrophobicity is enhanced, which can effectively improve the adhesion of asphalt to aggregates, improve the water stability of warm-mix asphalt mixtures, and avoid water damage to asphalt pavement. The modified vermiculite has better adsorption performance and can adsorb the generated toxic and harmful gases.
[0008] Acrylamide modified nano-silica, as a composite viscosity-reducing component, can effectively make up for the problem of insufficient viscosity-reducing effect of Ni-based expanded perlite in degrading waste plastics. Acrylamide modified nano-silica has a strong polar group, which can increase the ability of the viscosity-reducing warm-mix agent to form a strong polar hydrogen bond with the colloid asphalt, thereby destroying the aggregates produced after the degradation of the waste plastics, releasing the light components, and thus achieving the effect of viscosity reduction. The present invention utilizes the synergistic effect of each raw material component to successfully prepare a warm-mix agent with good viscosity-reducing effect, which can not only effectively improve the low-temperature performance of the warm-mix asphalt mixture, but also reduce energy consumption, further avoid the release of toxic and harmful gases, and the raw materials are cheap and easy to obtain, and no complex equipment needs to be added when used. The present invention effectively solves the problem that the addition of the warm-mix agent in the prior art causes the asphalt to have poor low-temperature ductility, resulting in insufficient crack resistance of the asphalt mixture and high cost of preparing the warm-mix agent, and provides a new design idea for the development of warm-mix asphalt mixtures.
[0009] Preferably, the waste plastics are PE waste plastics.
[0010] Preferably, the preparation method of the Ni-based expanded perlite comprises the following steps: S1. ball-milling the expanded perlite, heating it to 450° C.-500° C. and calcining it to obtain pretreated expanded perlite; S2. Evenly mix the pretreated expanded perlite and the nickel salt solution, perform a hydrothermal reaction at 120° C.-140° C., filter, and dry to obtain Ni-based expanded perlite.
[0011] Further preferably, in S1, the rotation speed of the ball mill is 300 rpm-500 rpm, and the ball milling time is 20 min-40 min.
[0012] Further preferably, in S1, the calcination time is 2h-3h.
[0013] Further preferably, in S1, the temperature is raised to 450°C-500°C by programmed heating, and the heating rate is 10°C / min-15°C / min.
[0014] Further preferably, in S2, the concentration of the nickel salt solution is 1 mol / L-2 mol / L, and the mass volume ratio of the pretreated expanded perlite to the nickel salt solution is 1 g:1 mL-1 g:2 mL.
[0015] Further preferably, in S2, the hydrothermal reaction time is 6h-8h.
[0016] Preferably, the specific preparation method of the fatty amine modified vermiculite powder comprises the following steps: immersing the vermiculite powder in an alkaline solution, filtering, and drying to obtain pretreated vermiculite powder; uniformly mixing the pretreated vermiculite powder with an alcohol solution of fatty amine, reacting at 75°C-90°C for 3h-5h, filtering, washing, and drying to obtain the fatty amine modified vermiculite powder.
[0017] More preferably, the vermiculite powder has a particle size of 100 μm-300 μm.
[0018] Further preferably, the alkaline solution is a 0.5 mol / L-1.5 mol / L potassium hydroxide solution.
[0019] Further preferably, the mass volume ratio of the vermiculite powder to the alkaline solution is 1g:2mL-1g:3mL.
[0020] More preferably, the immersion time is 3h-5h.
[0021] Further preferably, the mass concentration of the fatty amine in the alcohol solution of the fatty amine is 35%-50%, and the mass volume ratio of the pretreated vermiculite powder to the alcohol solution of the fatty amine is 1g:4mL-1g:6mL.
[0022] More preferably, the fatty amine is tetradecylamine or hexadecylamine.
[0023] Preferably, the preparation method of acrylamide-modified nano-silica comprises the following steps: Step a, dispersing nano-silica and a silane coupling agent in toluene, adjusting the pH to 8-9, performing ultrasonic treatment, filtering, and washing to obtain a modified nano-silica precursor; Step b: in an inert atmosphere, the modified nano-silica precursor and acrylamide are mixed and uniformly dispersed in toluene, an initiator is added, the mixture is reacted at 85° C.-90° C. for 12 h-18 h, filtered, washed, and dried to obtain acrylamide-modified nano-silica.
[0024] Further preferably, in step a, the silane coupling agent is KH570 or KH550.
[0025] Further preferably, in step a, the mass ratio of the silicon dioxide to the silane coupling agent is 10:1-10:3.
[0026] Further preferably, in step a, the mass volume ratio of the nano-silicon dioxide to the toluene is 1 g:3 mL-1 g:4 mL.
[0027] Further preferably, in step a, the temperature of the ultrasonic treatment is 70° C.-80° C., and the time of the ultrasonic treatment is 40 min-60 min.
[0028] Further preferably, in step b, the mass ratio of the modified nano-silica precursor to the acrylamide is 1:0.4-1:0.6.
[0029] Further preferably, in step b, the mass volume ratio of the modified nano-silica precursor to the toluene is 1 g:4 mL-1 g:6 mL.
[0030] Further preferably, in step b, the added amount of the initiator is 1wt%-3wt% of the mass of the modified nano-silica precursor.
[0031] Further preferably, in step b, the initiator is azobisisobutyronitrile.
[0032] Preferably, the anti-aging agent is RD.
[0033] The second aspect of the present invention provides a method for preparing the highly efficient viscosity-reducing warm mix agent, comprising the following steps: Step 1: Weigh Ni-based expanded perlite and waste plastic according to the designed ratio, mix them evenly, and perform a closed cracking reaction at 160° C.-180° C. in an inert atmosphere for 70 min-80 min to obtain a first mixture; Step 2, uniformly mixing the first mixture with acrylamide-modified nano-silica to obtain a viscosity reducer component; Step 3: Evenly mix the aliphatic amine modified vermiculite powder, the anti-aging agent and the viscosity reducing agent component to obtain a high-efficiency viscosity reducing warm mix agent.
[0034] The third aspect of the present invention provides a warm mix asphalt mixture, comprising the above-mentioned high-efficiency viscosity-reducing warm mix agent.
[0035] Preferably, the mixing temperature of the warm mix asphalt mixture is 120°C-140°C.
[0036] In summary, the present invention provides a kind of high-efficiency viscosity-reducing warm-mix agent, its preparation method and warm-mix asphalt mixture. The high-efficiency viscosity-reducing warm-mix agent uses Ni-based expanded perlite, fatty amine-modified vermiculite powder, acrylamide-modified nano-silica, anti-aging agent and waste plastic as raw material components, and utilizes the synergistic effect of each component to not only effectively reduce the mixing temperature of the asphalt mixture, but also ensure that the asphalt and the aggregate have good adhesion under the mixing conditions, improve the low-temperature performance of the warm-mix asphalt mixture, reduce energy consumption, and effectively reduce the release of harmful gases, which is safer and more environmentally friendly, and the raw materials are cheap and easy to obtain, and no other equipment is required when using it, and it is easy to operate. The technical solution of the present invention effectively solves the problems that the addition of warm-mix agent in the prior art causes the asphalt to have poor low-temperature ductility, resulting in insufficient crack resistance of the asphalt mixture and high preparation cost of the warm-mix agent. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1 This embodiment provides a high-efficiency viscosity-reducing warm mix agent and a preparation method thereof, which specifically includes the following contents: The high-efficiency viscosity-reducing warm mixing agent comprises the following raw material components in percentage by mass: 12% Ni-based expanded perlite, 55% fatty amine-modified vermiculite powder, 13% acrylamide-modified nano-silicon dioxide, 4% anti-aging agent RD and 16% PE waste plastics.
[0039] The preparation method of the high-efficiency viscosity-reducing warm mix agent comprises the following steps: Step 1: Weigh Ni-based expanded perlite and waste plastic according to the designed ratio, mix them evenly, add them into a closed cracking reactor, and perform a closed cracking reaction at 170° C. in an inert atmosphere for 75 minutes to obtain a first mixture; Step 2, uniformly mixing the first mixture with acrylamide-modified nano-silica to obtain a viscosity reducer component; Step 3: Evenly mix the aliphatic amine modified vermiculite powder, the anti-aging agent and the viscosity reducing agent component to obtain a high-efficiency viscosity reducing warm mix agent.
[0040] Wherein, the preparation method of the Ni-based expanded perlite comprises the following steps: S1. 50 g of expanded perlite was ball-milled at a rotation speed of 400 rpm for 30 min, placed in a muffle furnace, heated to 480° C. at a heating rate of 15° C. / min, and calcined for 2.5 h to obtain pretreated expanded perlite; S2. The pretreated expanded perlite was uniformly mixed with 80 mL of a 2 mol / L nickel nitrate solution, subjected to a hydrothermal reaction at 130° C. for 7 h, filtered, washed with deionized water for 3 times, and dried to obtain Ni-based expanded perlite.
[0041] The specific preparation method of the fatty amine modified vermiculite powder comprises the following steps: immersing 200 g of vermiculite powder with a particle size of 150 μm in 500 mL of 1 mol / L potassium hydroxide solution, filtering, and drying to obtain pretreated vermiculite powder; uniformly mixing the pretreated vermiculite powder with 1000 mL of an alcohol solution of hexadecylamine, reacting at 85° C. for 4 hours, filtering, washing, and drying to obtain the fatty amine modified vermiculite powder; wherein the mass concentration of hexadecylamine in the alcohol solution of hexadecylamine is 45%.
[0042] The preparation method of acrylamide-modified nano-silica comprises the following steps: Step a, dispersing 50g of nano-silica and 10g of silane coupling agent KH570 in 200mL of toluene, adjusting the pH to 8.3, performing ultrasonic treatment at 75°C for 50min, filtering, and washing twice with toluene to obtain a modified nano-silica precursor; Step b: Under an inert atmosphere, the modified nano-silica precursor is mixed with 25 g acrylamide, dispersed in 200 mL toluene, 1 g azobisisobutyronitrile is added, reacted at 90° C. for 14 h, filtered, washed twice with toluene, and dried to obtain acrylamide-modified nano-silica.
[0043] Example 2 This embodiment provides a high-efficiency viscosity-reducing warm mix agent and a preparation method thereof, which specifically includes the following contents: The high-efficiency viscosity-reducing warm mixing agent comprises the following raw material components in percentage by mass: 15% Ni-based expanded perlite, 45% fatty amine-modified vermiculite powder, 15% acrylamide-modified nano-silicon dioxide, 5% anti-aging agent RD and 20% PE waste plastics.
[0044] The preparation method of the high-efficiency viscosity-reducing warm mix agent comprises the following steps: Step 1: Weigh Ni-based expanded perlite and waste plastic according to the designed ratio, mix them evenly, add them into a closed cracking reactor, and perform a closed cracking reaction for 80 minutes at 160° C. in an inert atmosphere to obtain a first mixture; Step 2, uniformly mixing the first mixture with acrylamide-modified nano-silica to obtain a viscosity reducer component; Step 3: Evenly mix the aliphatic amine modified vermiculite powder, the anti-aging agent and the viscosity reducing agent component to obtain a high-efficiency viscosity reducing warm mix agent.
[0045] Wherein, the preparation method of the Ni-based expanded perlite comprises the following steps: S1. 50 g of expanded perlite was ball-milled at a speed of 500 rpm for 20 min, placed in a muffle furnace, and heated to 500° C. at a heating rate of 10° C. / min for calcination for 2 h to obtain pretreated expanded perlite; S2. The pretreated expanded perlite was uniformly mixed with 100 mL of 1 mol / L nickel nitrate solution, subjected to hydrothermal reaction at 140° C. for 6 h, filtered, washed with deionized water for 3 times, and dried to obtain Ni-based expanded perlite.
[0046] The specific preparation method of the fatty amine modified vermiculite powder comprises the following steps: immersing 200 g of vermiculite powder with a particle size of 300 μm in 500 mL of 1.5 mol / L potassium hydroxide solution, filtering, and drying to obtain pretreated vermiculite powder; uniformly mixing the pretreated vermiculite powder with 1000 mL of an alcohol solution of hexadecylamine, reacting at 85° C. for 4 hours, filtering, washing, and drying to obtain the fatty amine modified vermiculite powder; wherein the mass concentration of hexadecylamine in the alcohol solution of hexadecylamine is 50%.
[0047] The preparation method of acrylamide-modified nano-silica comprises the following steps: Step a, dispersing 50g of nano-silica and 10g of silane coupling agent KH550 in 220mL of toluene, adjusting the pH to 8.5, performing ultrasonic treatment at 80°C for 50min, filtering, and washing twice with toluene to obtain a modified nano-silica precursor; Step b: Under an inert atmosphere, the modified nano-silica precursor is mixed with 25 g acrylamide, dispersed in 250 mL toluene, 1 g azobisisobutyronitrile is added, reacted at 85° C. for 18 h, filtered, washed twice with toluene, and dried to obtain acrylamide-modified nano-silica.
[0048] Example 3 This embodiment provides a high-efficiency viscosity-reducing warm mix agent and a preparation method thereof, which specifically includes the following contents: The high-efficiency viscosity-reducing warm mixing agent comprises the following raw material components in percentage by mass: 10% Ni-based expanded perlite, 60% fatty amine-modified vermiculite powder, 103% acrylamide-modified nano-silicon dioxide, 3% anti-aging agent RD and 17% PE waste plastics.
[0049] The preparation method of the high-efficiency viscosity-reducing warm mix agent comprises the following steps: Step 1: Weigh Ni-based expanded perlite and waste plastic according to the designed ratio, mix them evenly, add them into a closed cracking reactor, and perform a closed cracking reaction for 70 minutes at 180° C. in an inert atmosphere to obtain a first mixture; Step 2, uniformly mixing the first mixture with acrylamide-modified nano-silica to obtain a viscosity reducer component; Step 3: Evenly mix the aliphatic amine modified vermiculite powder, the anti-aging agent and the viscosity reducing agent component to obtain a high-efficiency viscosity reducing warm mix agent.
[0050] Wherein, the preparation method of the Ni-based expanded perlite comprises the following steps: S1. Ball mill 50 g of expanded perlite at a rotation speed of 300 rpm for 40 min, place it in a muffle furnace, heat it to 480° C. at a heating rate of 12° C. / min, and calcine it for 3 h to obtain pretreated expanded perlite; S2. The pretreated expanded perlite was uniformly mixed with 80 mL of a 2 mol / L nickel nitrate solution, subjected to a hydrothermal reaction at 120° C. for 8 h, filtered, washed with deionized water for 3 times, and dried to obtain Ni-based expanded perlite.
[0051] The specific preparation method of the fatty amine modified vermiculite powder comprises the following steps: immersing 200 g of vermiculite powder with a particle size of 200 μm in 500 mL of 1 mol / L potassium hydroxide solution, filtering, and drying to obtain pretreated vermiculite powder; uniformly mixing the pretreated vermiculite powder with 1000 mL of an alcohol solution of hexadecylamine, reacting at 85° C. for 4 hours, filtering, washing, and drying to obtain the fatty amine modified vermiculite powder; wherein the mass concentration of hexadecylamine in the alcohol solution of hexadecylamine is 55%.
[0052] The preparation method of acrylamide-modified nano-silica comprises the following steps: Step a, dispersing 50g of nano-silica and 10g of silane coupling agent KH570 in 200mL of toluene, adjusting the pH to 9, performing ultrasonic treatment at 80°C for 50min, filtering, and washing twice with toluene to obtain a modified nano-silica precursor; Step b: Under an inert atmosphere, the modified nano-silica precursor is mixed with 25 g acrylamide, dispersed in 240 mL toluene, 1.2 g azobisisobutyronitrile is added, reacted at 88° C. for 16 h, filtered, washed twice with toluene, and dried to obtain acrylamide-modified nano-silica.
[0053] Comparative Example 1 This comparative example provides a viscosity-reducing warm-mix agent, which differs from Example 1 in that the fatty amine-modified vermiculite powder is replaced with an equal amount of vermiculite powder, and other components and processes remain unchanged, which will not be described in detail here.
[0054] Comparative Example 2 This comparative example provides a viscosity-reducing warm-mix agent, which differs from Example 1 in that the Ni-based expanded perlite is replaced with an equal amount of Ni-based zeolite, and other components and processes remain unchanged, which will not be described again.
[0055] Comparative Example 3 This comparative example provides a viscosity-reducing warm-mix agent, which differs from Example 1 in that the acrylamide-modified nano-silicon dioxide is replaced with an equal amount of nano-silicon dioxide, and other components and processes remain unchanged, which will not be described in detail here.
[0056] In order to further demonstrate the technical effect of the present invention, the present invention conducted performance tests on the viscosity-reducing warm mix agents obtained in Examples 1-3 and Comparative Examples 1-3, and applied them to base asphalt to prepare asphalt mixtures. The specific operations are shown in the test examples.
[0057] Test example Heat the base asphalt to a fluid state, add a viscosity-reducing warm-mix agent at 4 wt% of the base asphalt mass, set the mixing temperature to 135°C, mix for 1.5 minutes, and obtain warm-mix asphalt; Heat the aggregates of various particle sizes to constant temperature and constant weight in advance, set the temperature to 145°C, and heat the matrix asphalt to a flowing state in advance to avoid repeated long-term heating that causes aging. Put the heated stones and matrix asphalt into the mixer respectively, set the mixer temperature to 135°C, mix for 0.5 minutes, add 4wt% of the matrix asphalt mass of viscosity-reducing warm mixing agent, mix for 1.5 minutes, then add mineral powder and continue mixing for 1 minute to obtain warm-mix asphalt mixture.
[0058] The penetration, softening point and ductility of the warm mix asphalt were tested according to JTG E20-2011 "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results are shown in Table 1; According to the test method in JTG E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering", the dynamic stability, water immersion residual stability ratio and freeze-thaw splitting strength ratio of the obtained warm mix asphalt mixture molded Marshall specimens were tested. The test results are shown in Table 2.
[0059] Table 1 Performance test results of warm mix asphalt prepared by using the viscosity reducing warm mix agent obtained in each embodiment and comparative example
[0060] Table 2 Performance test results of warm mix asphalt mixtures prepared using the viscosity reducing warm mix agents obtained in various embodiments and comparative examples
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-efficiency viscosity-reducing warm mixing agent, characterized in that: The invention comprises the following raw material components in percentage by weight: 10%-15% of Ni-based expanded perlite, 45%-60% of aliphatic amine-modified vermiculite powder, 10%-15% of acrylamide-modified nano-silicon dioxide, 3%-5% of anti-aging agent and the remainder of waste plastics.
2. The high-efficiency viscosity-reducing warm mix agent according to claim 1, characterized in that: The preparation method of the Ni-based expanded perlite comprises the following steps: S1. ball-milling the expanded perlite, heating it to 450° C.-500° C. and calcining it to obtain pretreated expanded perlite; S2. Evenly mix the pretreated expanded perlite and the nickel salt solution, perform a hydrothermal reaction at 120° C.-140° C., filter, and dry to obtain Ni-based expanded perlite.
3. The high-efficiency viscosity-reducing warm mix agent as claimed in claim 2, characterized in that: In S1, the ball milling speed is 300 rpm-500 rpm, and the ball milling time is 20 min-40 min; and / or In S1, the calcination time is 2h-3h; and / or In S1, the temperature is raised to 450°C-500°C by programmed heating, and the heating rate is 10°C / min-15°C / min.
4. The high-efficiency viscosity-reducing warm mix agent according to claim 2, characterized in that: In S2, the concentration of the nickel salt solution is 1 mol / L-2 mol / L, and the mass volume ratio of the pretreated expanded perlite to the nickel salt solution is 1 g:1 mL-1 g:2 mL; and / or In S2, the hydrothermal reaction time is 6-8h.
5. The high-efficiency viscosity-reducing warm mix agent according to claim 1, characterized in that: The specific preparation method of the fatty amine modified vermiculite powder comprises the following steps: immersing the vermiculite powder in an alkaline solution, filtering, and drying to obtain pretreated vermiculite powder; uniformly mixing the pretreated vermiculite powder with an alcohol solution of fatty amine, reacting at 75°C-90°C for 3h-5h, filtering, washing, and drying to obtain the fatty amine modified vermiculite powder.
6. The high-efficiency viscosity-reducing warm mix agent according to claim 5, characterized in that: The vermiculite powder has a particle size of 100 μm-300 μm; and / or The alkaline solution is a 0.5 mol / L-1.5 mol / L potassium hydroxide solution; and / or The immersion time is 3h-5h; and / or The mass concentration of the fatty amine in the alcohol solution of the fatty amine is 35%-50%, and the mass volume ratio of the pretreated vermiculite powder to the alcohol solution of the fatty amine is 1g:4mL-1g:6mL.
7. The high-efficiency viscosity-reducing warm mix agent according to claim 1, characterized in that: The preparation method of acrylamide-modified nano-silica comprises the following steps: Step a, dispersing nano-silica and a silane coupling agent in toluene, adjusting the pH to 8-9, performing ultrasonic treatment, filtering, and washing to obtain a modified nano-silica precursor; Step b: in an inert atmosphere, the modified nano-silica precursor and acrylamide are mixed and uniformly dispersed in toluene, an initiator is added, the mixture is reacted at 85° C.-90° C. for 12 h-18 h, filtered, washed, and dried to obtain acrylamide-modified nano-silica.
8. The high-efficiency viscosity-reducing warm mix agent according to claim 7, characterized in that: In step a, the silane coupling agent is KH570 or KH550; and / or In step a, the mass ratio of the silicon dioxide to the silane coupling agent is 10:1-10:3; and / or In step a, the mass volume ratio of the nano-silicon dioxide to the toluene is 1 g:3 mL-1 g:4 mL; and / or In step a, the temperature of the ultrasonic treatment is 70°C-80°C, and the time of the ultrasonic treatment is 40min-60min; and / or In step b, the mass ratio of the modified nano-silica precursor to the acrylamide is 1:0.4-1:0.6; and / or In step b, the mass volume ratio of the modified nano-silica precursor to the toluene is 1g:4mL-1g:6mL; and / or In step b, the amount of the initiator added is 1wt%-3wt% of the mass of the modified nano-silica precursor.
9. The method for preparing the high-efficiency viscosity-reducing warm mix agent according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Weigh Ni-based expanded perlite and waste plastic according to the designed ratio, mix them evenly, and perform a closed cracking reaction at 160° C.-180° C. in an inert atmosphere for 70 min-80 min to obtain a first mixture; Step 2, uniformly mixing the first mixture with acrylamide-modified nano-silica to obtain a viscosity reducer component; Step 3: Evenly mix the aliphatic amine modified vermiculite powder, the anti-aging agent and the viscosity reducing agent component to obtain a high-efficiency viscosity reducing warm mix agent.
10. A warm mix asphalt mixture, characterized in that: The invention comprises the high-efficiency viscosity-reducing warm mixing agent as described in any one of claims 1 to 8.